Electrochemical Studies of 1,5-Diphenylcarbazide - Kaparwan, Ajay; Singh, Nitin; Singh, Keshav; Dubey, R.S. (Asian Journal of Chemistry, 2012)
Electrochemical behaviour of 1,5-diphenylcarbazide has been investigated to determine the redox process at hanging mercury electrode by using differential pulse voltammetry and cyclic voltammetry. A series of studies were performed with various parameters such as pH, different supporting electrolyte and photochemical oxidation process. Studies performed in both acidic and alkaline buffer solutions revealed cathodic reduction of the carbonyl group (C=O) present in the compound at -1.20 V vs. S.C.E. proton abstraction in alkaline buffer solution resulted in cathodic reductions of both the oxidation products of 1,5-diphenylcarbazide at -0.3 V and -0.6 V vs. S.C.E. Studies performed in supporting electrolytes such as, KNO3 and HClO4 showed the oxidation prone sensitive nature of 1,5 diphenylcarbazide towards the oxidizing ability of anions like NO3– and ClO4– present in supporting electrolyte. Photochemical oxidation was triggered at lower concentrations of 1,5-diphenylcarbazide, which oxidizes to 1,5-diphenylcarbadiazone. It subsequently reduces to 1,5-diphenylcarbazone and 1,5-diphenylcarbazide.